Numerical solutions of the unsteady Fanno model for compressible pipe flow - Ockendon, J; Ockendon, H; Novikovs, A (2007)
This paper presents numerical results on the evolution of the solutions of the Fanno model for compressible pipe flow. The principal results concern the large-time behaviour when nonlinear effects are appreciable throughout the evolution. Our computations show that compression waves can be expected to evolve into travelling waves for large times whereas expansion waves cannot.